Neurodegenerative Process Linking the Eye and the Brain - Mancino, Raffaele; Cesareo, Massimo; Martucci, Alessio; Di Carlo, Emiliano; Ciuffoletti, Elena; Giannini, Clarissa; Morrone, Luigi A.; Nucci, Carlo; Garaci, Francesco (Current Medicinal Chemistry, 2019)
Recent literature agrees that neurodegenerative processes involve both the retina and the central nervous system, which are two strictly related anatomical structures. However, the causal mechanisms of this dual involvement are still uncertain. To date, anterograde transsynaptic neurodegeneration, triggered by retinal ganglion cells’ death, and retrograde transsynaptic neurodegeneration, induced by neurodegenerative processes of the central nervous system, has been considered the major possible causal mechanisms. The development of novel neuroimaging techniques has recently supported both the study of the central stations of the visual pathway as well as the study of the retina which is possibly an open window to the central nervous system.
Keywords: Alzheimer